Vibrational contributions to vicinal proton-proton coupling constants3JHH - Esteban, Angel L. (2010)
Vibrational contributions to the 3JHH couplings of six mono- and five 1,1-di-substituted ethanes, three mono-substituted cyclohexanes, three norbornane-type molecules, and 11 three-membered rings have been calculated at the DFT/B3LYP level for the Fermi contact term using a moderate sized basis set. When, for a data set of 70 couplings, the sums of the values for the equilibrium configurations Je and the respective vibrational contributions J300vib at 300K are multiplied by a factor of 0.8485, the corresponding predicted couplings Jpre are in good agreement with the experimental couplings Jexp with a standard deviation σ of 0.18 Hz. The same σ results when J pre values are obtained by multiplying the Je values by 0.9016. However, the vibrational contributions must be taken into account, together with the Je values, in order to achieve a procedure for a reliable and accurate prediction of 3JHH couplings since, globally, J300vib contributions amount to about 7% of the Je values and the correlation coefficient between J 300vib and Je is only 0.68 with a σ deviation of 0.20. The first and diagonal second derivatives of J with respect to each normal coordinate Qk, required to estimate the vibrational contributions, have been obtained from six Jk values computed for molecular geometries positively (+δQk) and negatively (-δQk) displaced from the equilibrium geometry along the normal coordinate Qk and using for δ the values 0.01, 0.05 and 0.10. The computational precision of the results obtained when using one, two and three δ values is analysed. © 2010 Taylor & Francis.